A need analysis for developing multi-representation assessment instruments assisted by Thunkable to measure argumentation skills in fluid materials - Gustina, Emi; Viyanti, Viyanti; Herlina, Kartini (Indonesian Journal of Science and Mathematics Education, 2025)
Scientific argumentation is a critical 21st-century skill that must be systematically integrated into science education, particularly physics. However, current classroom assessments rarely comprehensively and in-depth measure students’ argumentation skills. This study aims to analyze the need to develop a multi-representation assessment instrument supported by the Thunkable application to evaluate students’ scientific argumentation skills on static fluid concepts. A mixed-method approach with an embedded sequential design was employed. Quantitative data were collected through questionnaires administered to 34 physics teachers and 97 eleventh-grade students from several high schools in Lampung Province, Indonesia. Besides, qualitative data were obtained through open-ended responses to explore classroom learning experiences and assessment practices further. The findings reveal that 91% of teachers reported difficulties in assessing argumentation skills, while 94% of students faced challenges in connecting static fluid concepts across different representations. The use of multi-representation tasks in assessments was found to be limited. Nevertheless, teachers and students expressed strong interest in using interactive digital assessment tools. These findings highlight the strategic opportunity to develop a Thunkable-assisted, multi-representation-based assessment instrument that addresses teachers’ and students’ needs and improves assessment practices in physics education by promoting meaningful learning and scientific argumentation.